Reactogenicity to a Live Attenuated Varicella Vaccine in Canadian Children. (1st April 2000) - Diaz-Mitoma, Francisco; Halperin, Scott A; Scheifele, David
Abstract : OBJECTIVE: To assess the reactogenicity and safety of a thermostable, high titre, varicella vaccine in healthy infants and children. DESIGN: Open study of 505 children monitored for 42 days after vaccination. SETTING: Three urban Canadian centres (Halifax, Ottawa and Vancouver). PARTICIPANTS: 505 healthy children one to 12 years of age were enrolled and 504 completed the study. All were susceptible to varicella by history. INTERVENTIONS: All participants received one dose of live attenuated varicella vaccine (1×10 4.5 plaque forming units/dose) subcutaneously. MAIN OUTCOME MEASURES: The children were monitored from the day of vaccine administration (day 0) until day 42. All local and general symptoms and signs were recorded on diary cards by the patients? parents, who were encouraged to fill in the cards on days 2 to 3 and 18 to 24 via telephone calls from study personnel. RESULTS: Most of the symptoms noted after vaccine administration were mild and transient, and all resolved within the respective follow-up periods. Injection site symptoms included pain (17.5%, 13.9% and 30.4% in centres 1, 2 and 3 respectively), redness (21.1%, 32.1% and 48.8%) and swelling (7%, 10.3% and 29.2%). The general symptoms reported were fever 37.5°Cor higher (3.5%, 4.8% and 3.0%) and varicella-like rashes (6.4%, 2.4% and 0%). Two subjects had severe symptoms (one with cervical lymphadenopathy, and one with a fever higher than 39°C) probably related to vaccine administration. No serious adverse events were reported during the entire study. CONCLUSION: The vaccine was well tolerated.